Treatment strategies in coronary microvascular dysfunction: A systematic review of interventional studies. (15th April 2019) - Suhrs, Hannah E.; Michelsen, Marie M.; Prescott, Eva
Abstract: CMD has been associated with a wide spectrum of diseases and conditions, and it has proven to be a strong prognostic marker of morbidity and mortality. Despite increased attention, guideline‐based treatment recommendations are lacking. We performed a systematic review of pharmacological and nonpharmacological interventions to improve coronary perfusion, assessed by IC Doppler, TTDE, PET, CMRI, transthoracic contrast perfusion echocardiography, and dilution techniques. No restrictions were made regarding the study design (randomized, placebo‐controlled/randomized with active comparators/nonrandomized with or without a control group), the cardiac condition studied, or the coronary microvascular function at baseline. An electronic database search yielded 4485 records of which 80 studies met our inclusion criteria. Included studies were sorted according to intervention and study design. Studies were small and heterogeneous in methodology, and only few were placebo‐controlled. Although some treatments looked promising, we found that no specific treatment was sufficiently well documented to be recommended in any patient groups. There is a need for larger well‐designed clinical trials, and we suggest that future studies stratify study populations according to pathogenic mechanisms, thereby investigating whether an individualized treatment approach would be more successful.